Architecture of geothermal places: socially and culturally responsive therapeutic landscapes. Issue 1 (2nd January 2021) - McIntosh, Jacqueline; Marques, Bruno; Fairbrother, Kezia
ABSTRACT: There is increasing recognition that culture plays a crucial role in shaping therapeutic environments; from fundamental conceptions of wellness and healing, through to cultural relationships with the natural world, and to how spaces are shaped by culturally-specific construction methods and materials. This paper approaches the concept of therapeutic landscapes from an architectural perspective, analysing three separate case studies relating to geothermal architecture from the Ring of Fire. It attempts to bridge a gap in the literature regarding geothermal therapeutic landscapes, by understanding these places not purely as 'blue spaces' but rather as socio-cultural encounters which influence material and physical architectural conditions. This paper contributes to our understanding of the role of culture in producing and maintaining architectural places by reflecting on the way in which individuals and groups engage with place, their range of social encounters, experiences, narratives, affective beliefs, and embodiments that combine with architectural materiality and the associated complex culturally-produced meanings.